Complementary treatment to reduce blood sugar levels of type 2 diabetes mellitus patients - Jujuk Proboningsih; Anita Joeliantina; Aida Novitasari; Dewi Purnamawati (International Journal of Public Health Science (IJPHS), 2020)
Diabetes mellitus is a chronic disease that requires long-term management. There is a tendency in type 2 diabetes mellitus patients to use herbs as a complement to medical treatment. The purpose of this study was to analyze the use of herbs as a complement to medical treatment in reducing blood sugar levels of T2DM patients. This type of research is quasi-experimental, with 40 research subjects divided into 4 groups. Determination of research subjects by purposive sampling in accordance with established inclusion criteria. Data analysis using paired T test. The majority of respondents was women (77.5%) and had no genetic history (75%). The duration of type 2 diabetes mellitus  majority was >5 years 72.5%). Data on random blood sugar levels before (p=0.098) and after (p=0.113) intervention were normally distributed and homogeneous p>0.05 (0.839). The treatment group (groups 2, 3, and 4) showed a significant decrease in random blood sugar levels as the control group (1) with a significance value <0.05. Giving herbs has a tendency to reduce random blood sugar levels when used as a complement to medical treatment. Bitter melon shows the effect of decreasing random blood sugar levels greater than the provision of bay leaves and cinnamon.